Pengaruh Sikap Karyawan terhadap Pencapaian Tujuan Industri Hotel di Madura: The Influence of Employee Attitudes on the Achievement of Hotel Industry Goals in Madura - Iriani Ismail (Fenomena, 2003)
The rapid growth of the global tourism sector demands superior service quality in the hospitality industry, yet many hotels in developing regions struggle to align employee attitudes with organizational goals. This study examines how employee attitudes—specifically salary, management leadership, promotion opportunities, and working conditions—affect the achievement of hotel industry objectives in Madura, Indonesia. Primary data were collected through purposive sampling from nine non-star hotels across four districts. Using multiple linear regression, the findings show that all four variables simultaneously have a significant positive effect on goal achievement at the 5% level. Among these, employee salary emerges as the dominant factor influencing organizational success, followed by promotion, leadership, and working conditions. The study concludes that improving salary structures is the most critical intervention for hotel management to enhance employee attitudes and achieve customer-oriented business development. Recommendations include evaluating compensation policies, fostering strategic leadership, and designing non-linear models for future research. Pertumbuhan pesat sektor pariwisata global menuntut kualitas layanan unggul di industri perhotelan, namun banyak hotel di daerah berkembang masih menghadapi kendala dalam menyelaraskan sikap karyawan dengan tujuan organisasi. Penelitian ini mengkaji hubungan antara sikap karyawan—terutama gaji, kepemimpinan manajemen, promosi, dan kondisi kerja—dengan pencapaian tujuan industri hotel di Madura. Data primer dikumpulkan secara purposive sampling dari sembilan hotel melati di empat kabupaten. Dengan analisis regresi linear berganda, hasil penelitian menunjukkan bahwa keempat variabel secara simultan berpengaruh positif dan signifikan pada taraf 5%. Secara parsial, gaji karyawan merupakan faktor dominan yang mempengaruhi keberhasilan organisasi, diikuti promosi, kepemimpinan, dan kondisi kerja. Penelitian menyimpulkan bahwa peningkatan struktur gaji merupakan intervensi paling kritis bagi manajemen hotel untuk memperbaiki sikap karyawan guna mencapai pengembangan usaha yang berorientasi pelanggan. Rekomendasi mencakup evaluasi kebijakan kompensasi, pengembangan kepemimpinan strategis, dan perancangan model non-linear untuk penelitian selanjutnya.